Pre-war photographic negatives in the collection of the Bakhchisarai Museum–Reserve: objects and expositions of the Khan’s Palace in the 1920s–1930s - Sevilya Velieva (Крымское историческое обозрение)
The article examines the collection of photographic negatives from the funds of the Bakhchisarai Museum-Reserve, which is the most valuable material for a wide range of researchers. It contains architectural monuments (Khan’s Palace, mosques, fountains, mausoleums, residential buildings, etc.), museum staff, cultural and educational figures, residents of Bakhchisarai, villages of Crimea, museum objects that have not survived to the present day. Special attention is paid to the images of the museum’s exhibitions in the 1920s and 1930s.